Effect of hot pressing temperature on microstructure, mechanical properties and grinding performance of vitrified-metal bond diamond wheels. (January 2016) - Song, Dongdong; Wan, Long; Liu, Xiaopan; Hu, Weida; Xie, Delong; Wang, Junsha
Abstract: The self-sharpening vitrified-metal bond diamond wheels added with a 3 wt.% brittle Na2 O-B2 O3 -SiO2 -Al2 O3 -Li2 O vitrified bond were fabricated by hot pressed sintering technique. Using the methods of scan-electroscope, energy spectrum analysis, X-diffraction analysis, XPS analysis, Rockwell hardness test and three-point bending test, the effects of hot pressing temperature on the microstructure, hardness and the transverse rupture strength (TRS) of vitrified-metal bond were investigated. Then the grinding performance of cylinder of the diamond wheels was also studied. The results showed that, when the hot pressing temperature was 850 °C, a thin FeAl2 O4 transition layer formed, which enhanced the interfacial bending strength between metal and glass phase, and the TRS of vitrified-metal bond reached the maximum value 826.54 MPa. Comparing with metal bond diamond wheel's, the average value of the roundness and straightness of the 50 cylinders ground by the vitrified-metal diamond wheel reduced from 3.1 μm and 2.5 μm to 2.7 μm and 2.1 μm. Highlights: 3 wt.% glass was added in metal bond diamond wheels to improve its self-sharpening. 10–20 nm FeAl2 O4 transfer layer enhanced the interfacial bending strength at 850 °C. TRS of glass-metal bond reached the maximum value 826.54 MPa at 850 °C. Surface quality of cylinders grinded by glass-metal bond wheels was improved.